Add-On Effects of Chinese Herbal Medicine for Post-Stroke Spasticity: A Systematic Review and Meta-Analysis - Cai, Yiyi; Zhang, Claire Shuiqing; Liu, Shaonan; Wen, Zehuai; Zhang, Anthony Lin; Guo, Xinfeng; Xue, Charlie Changli; Lu, Chuanjian (Frontiers in Pharmacology, 2019)
Background: Treatment for post-stroke spasticity (PSS) remains a big challenge in clinical practice. Chinese herbal medicine (CHM) is often administered assisting the routine care (RC) in the treatment of PSS with increasing number of clinical research and preclinical studies suggesting potential benefits. Therefore, we conducted this systematic review and meta-analysis to evaluate the add-on effects and safety of CHM for PSS. Methods: Five English and four Chinese databases were searched from their inceptions to February 2018. We included randomized controlled trials evaluating the add-on effects of CHM for PSS based on change scores of (Modified) Ashworth Scale (AS or MAS), Fugl-Meyer Assessment of Sensorimotor Recovery (FMA) and Barthel Index (BI). Results: Thirty-five trials involving 2,457 patients were included. For upper-limb AS or MAS, the estimated add-on effects to RC were significantly better using oral (SMD-1.79, 95%CI [-3.00,-0.57]) or topical CHM (SMD-1.06, 95%CI [-1.40,-0.72]). For lower-limb AS or MAS, significant add-on benefits to RC were also detected (SMD-1.01, 95%CI [-1.43,-0.59] and SMD-1.16, 95%CI [-1.83,-0.49]) using oral and topical CHM respectively. For FMA and BI, better results were detected by adding CHM to RC except for the subgroup of oral CHM for upper-limb FMA. Ten out of the 35 included studies reported safety information with two of them mentioned two mild adverse events. Conclusions: Noting the quality concerns of the included trials, this review suggested that CHM appeared to be a promising, well-tolerated add-on therapy to RC for reducing spasticity and improving PSS patients’ daily activities.